2016
DOI: 10.5350/sleep.hypn.2016.180103
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems and the Phenomenological Factors of Dreaming

Abstract: This study aims to provide a preliminary overview of how specific sleep problems might have differential impacts on the phenomenological properties of dreaming. The sample contained 186 upper secondary school students, whose subjective intensity of dream experiences, thematic dream content, and sleep disturbances were assessed using the Dream Intensity Scale, Dream Motif Scale, and Sleep Habits Questionnaire, respectively. The overall evidence suggests that most sleep problems, except sleep bruxism, sleepwalki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The findings of the current study largely resonate with those of Yu and Thompson's (2016) study. In both studies, restless legs, disrupted circadian rhythm, and sleeptalking were the most prevalent sleep problems, whereas respiratory pauses, cataplexy, and sleepwalking were the rarest.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The findings of the current study largely resonate with those of Yu and Thompson's (2016) study. In both studies, restless legs, disrupted circadian rhythm, and sleeptalking were the most prevalent sleep problems, whereas respiratory pauses, cataplexy, and sleepwalking were the rarest.…”
Section: Discussionsupporting
confidence: 86%
“…The OCI-R total score positively predicted the SHQ total score, sleep paralysis, and restless legs. Yu and Thompson (2016) demonstrated that each sleep problem has a distinct pattern of associations with the phenomenological properties of dreaming. Nevertheless, waking-life emotionality, to which both sleep problems and dream experiences are sensitive, might decisively mediate the relationship.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations